Bio-stimulatory effects of bull urine (BU), PRID and GnRH on hormonal profile and association with blood minerals in pubertal anestrus Sahiwal heifers - AHMED, ABRAR; TIWARI, R P; KHAN, J R; TIWARI, S P; MISHRA, G K (The Indian Journal of Animal Sciences, 2017)
The present study was designed to assess the bio-stimulatory effect of bull urine (BU) exposure, administration of progesterone impregnated intravaginal device (PRID) in combination with PGF2α and gonadotropin releasing hormone (PRID-PG-GnRH), and GnRH in combination with PGF2α (GnRH-PG-GnRH) on alteration of hormonal profile in correlation with induction of estrus in pubertal anestrus Sahiwal heifers. Pubertal anestrus Sahiwal heifers (32) were randomly divided into 4 groups, viz. group 1 (8; BU), group 2 (8; PRID-PG-GnRH), group 3 (8; GnRHPG- GnRH) and group 4 (8; Control). Treatment with PRID-PG-GnRH and GnRH-PG-GnRH significantly increased the serum progesterone and estrogen concentration whereas, in BU and untreated control heifers, the progesterone concentration remained at the basal level during 30 days observation period. However, a meager increase of serum estrogen concentration was observed from day 9 and 11 in BU treated heifers. The association of certain macro and micro minerals level in blood during pre and post treatment period was studied to correlate the treatment response. Significant difference was observed in mean serum calcium (mg/dl) and iron (ppm) levels in pre and post BU exposed, PRID-PG-GnRH and GnRH-PG-GnRH treated heifers compared to the control. No significant difference in mean serum phosphorus (mg/dl), copper (ppm) and cobalt (ppm) level was observed in all the groups. Significant difference was observed in mean serum magnesium (mg/dl) and zinc levels in pre and post PRID-PG-GnRH and GnRH-PG-GnRH treated heifers as compared to BU exposed and control heifers. Thus, it can be concluded that the treatment with PRID-PG-GnRH and GnRH-PG-GnRH had more pronounced effect on induction of estrus as reflected by increased level of serum estradiol on day 9 and progesterone level on 10th day post AI than the bull urine treated and control heifers and subsequent increase in serum calcium, magnesium, iron, and zinc levels during post treatment period in pubertal anestrus Sahiwal heifers.